Low-temperature all-solid-state lithium-ion batteries based on a di-cross-linked starch solid electrolyte. Issue 59 (28th October 2019) - Lin, Zehua; Liu, Jin
Abstract : The all-solid-state lithium battery based on di-cross-linked starch electrolyte is applicable at low temperature. Abstract : The preparation of a low-temperature solid electrolyte is a challenge for the commercialization of the all-solid-state lithium-ion battery (ASSLIB). Here we report a starch-based solid electrolyte that displays phenomenal electrochemical properties below room temperature (RT). The starch host of the electrolyte is synthesized by two cross-linking reactions, which provide sufficient and orderly binding sites for the lithium salt to dissolve. At 25 °C, the solid electrolyte has exceptional ionic conductivity ( σ, 3.10 × 10 −4 S cm −1 ), lithium-ion transfer number ( t +, 0.82) and decomposition potential (dP, 4.91 V). At −20 °C, it still has outstanding σ (3.10 × 10 −5 S cm −1 ), t + (0.72) and dP (5.50 V). The LiFePO4 ASSLIB assembled with the electrolyte exhibits unique specific capacity and long cycling life below RT, and the LiNi0.8 Co0.1 Mn0.1 O2 ASSLIB can operate at 4.3 V and 0 °C. This work provides a solution to solve the current challenges of ASSLIBs to widen their scope of applications.